Relationship between Self-care Behaviors and Quality of Life among Hypertensive Patients Visiting Comprehensive Health Centers in Hamadan, Iran - Shayesteh Bairami; Yadollah Fathi; Samaneh Mohammadinasab; Majid Barati; Younes Mohammadi (Journal of Education and Community Health)
Background and Objectives: Non-adherence to self-care behaviors can deteriorate quality of life among hypertension patients. Thus, we sought to examine the association between self-care behaviors and quality of life among patients with hypertension visiting Comprehensive Health Centers in Hamadan, Iran. Materials and Methods: This descriptive, cross-sectional study was carried out in 200 hypertensive patients presenting to Comprehensive Health Centers in Hamadan, Iran, 2017. The participants were recruited using multistage sampling method. A demographic form, Self-Care Behaviors Scale, and the Quality of Life (SF-36) questionnaire were used to collect the data. Pearson correlation coefficient, t-test, and One-way analysis of variance were run to analyze the data in SPSS, version 16. Results: The self-care behavior and quality of life overall scores were respectively 63.5% and 56.6%, indicating that they were at admissible and inadmissible levels, respectively. There was a significant relationship between quality of life and gender, marital status, and body mass index (BMI; P<0.05). Also, there was a positive significant correlation between self-care behavior and three dimensions of quality of life, including physical status, emotional well-being, and bodily pain (P<0.05). Further, there was a positive significant correlation between self-care behavior and total score of quality of life (P=0.005; r=0.196). Conclusion: Considering the relationship of quality of life with well-being and self-care behaviors, we recommend designing and implementing educational programs for hypertensive patients to increase adherence to self-care behaviors.